Seasonal dynamics of dissolved organic matter in a small tropical estuary-coastal bay continuum: distribution, transformation, flux, and global perspectives - Pengfei Liu; Kuan Jiang; Qi Tan; Fajin Chen; Renming Jia; Chao Wang; Chao Wang; Chao Wang; Chao Wang (Frontiers in Marine Science)
The export and transformation of riverine dissolved organic matter (DOM) at the river-sea interface are critical to understanding carbon budgets in tropical regions, yet remain underexplored in small watersheds. This study analyzed dissolved organic carbon (DOC), chromophoric (CDOM), and fluorescent DOM (FDOM) over five cruises from summer 2021 to summer 2022 in the Suixi Estuary-Zhanjiang Bay continuum, a eutrophic tropical transition zone in the northwestern South China Sea. Seasonal variations were pronounced for DOM in the continuum and two endmembers. Freshwater DOM, dominated by terrestrial organic materials, was closely tied to soil leaching and erosion, correlating with precipitation patterns. Conversely, seawater DOM, enriched in protein-like FDOM, varied with the West-Guangdong Coastal Current and its associated primary production. Linear decreases in DOM with increasing salinity indicate that conservative mixing largely shapes DOM distributions in the continuum, especially for humic-like FDOM. Non-conservative processes, including flocculation, phytoplankton production, and microbial transformation, variably alter DOM components across seasons. The Suixi River in summer contributed considerably but disproportionately to the annual DOM flux (47-59%), due to intense soil leaching processes that mobilize refractory terrigenous DOM. The deviation observed in the Suixi River’s DOC-CDOM relationship from that of global rivers, coupled with a distinctive single-peak pattern between the carbon-specific absorption coefficient and water yield in global rivers, highlights the critical role of watershed nature in influencing river-exported DOM composition. The notably high DOC and CDOM yields for the Suixi River further emphasize the importance of small, tropical rivers in shaping the estuarine and coastal carbon budget.